Legal protection of personal data in e-commerce online transactions with the paylater method - Erix Purwanto; Muhamad Wildan Adzikri; Choerul Gilang Permana; Tina Marlina; Rd. Handiriono (Interdisciplinary Social Studies, 2024)
The internet has been widely used in Indonesia as a support for communication and information in various electronic media. The rapid development of the times makes technology even more increasing. This gave rise to several e-commerce applications in online sales and purchases  such as Shopee, Tokopedia, Akulaku, Traveloka, and many others, some of these  e-commerce  applications have features that can make it easier for consumers to make buying and selling transactions, namely the Paylater feature. The focus of this research is to find out about the legal protection of personal data to consumers and the efforts made to the parties in an e-commerce transaction  using the PayLater method. This research uses the Normative Juridical method and applies legislative and conceptual approaches. The results of the research obtained found that legal protection for PayLater Credit service users is contained in the regulations of Law No. 8 of 1999 concerning Consumer Protection, POJK Number 77 / POJK.01 / 2016 and Law No. 19 of 2016 concerning Electronic Information and Transactions. And in Law Number 27 of 2022 concerning Personal Data Protection. Meanwhile, PayLater Credit dispute resolution is more effectively implemented with the APS (Alternative Dispute Resolution) method, one of which is by creating a PSD (Online Dispute Resolution) institution.